Simple Coordination and Cognitive Stimulation Activities for Cognitive Function Assessments using Functional Near-Infrared Spectroscopy - NORSHAM JULIANA; IZUDDIN FAHMY ABU; MOHAMAD HAIQAL NIZAR MOHAMAD; MUHAMMAD FATTAH FAZEL; NURUL ATHIRAH RANI; NUR ZAFIRAH FARHANA ZAFREEN; NOR AZILA NOH; ZALHAN MD YUSUF; MUHAMMAD HAFIZ LAILI; SRIJIT DAS (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by WOS/Scopus/ERA/MyCite